Obstructive or non-obstructive megacystis: a prenatal dilemma - Mandaletti, Martina; Cerchia, Elisa; Ruggiero, Elena; Teruzzi, Elisabetta; Bastonero, Simona; Pertusio, Annasilvia; Della Corte, Marcello; Sciarrone, Andrea; Gerocarni Nappo, Simona (Frontiers in Pediatrics, 2024)
Diagnosis of prenatal megacystis has a significant impact on the pregnancy, as it can have severe adverse effects on fetal and neonatal survival, renal and pulmonary function. The aim of the study is to investigate natural history of fetal megacystis, to try to differentiate in utero congenital lower urinary tract obstruction (LUTO) from non-obstructive megacystis, and, possibly, to predict postnatal outcome.A retrospective single center observational study was conducted from July 2015 to November 2023. Inclusion criteria was a longitudinal bladder diameter (LBD)> 7 mm in the first trimester or an overdistended / thickened walled bladder failing to empty in the second and third trimester. Close ultrasound follow-up, multidisciplinary prenatal counselling, invasive and non-invasive genetic tests were offered. Informed consent for fetal autopsy was obtained in the event of pregnancy termination or intrauterine fetal demise (IUFD). After birth, neonates were followed up at the same center. Patients were stratified according diagnosis: LUTO (G1), urogenital anomalies other than LUTO ("non-LUTO") (G2) and normal urinary tract (G3).Twenty-seven fetuses were included in the study, 26 males. Megacystis was diagnosed in the second and third trimester in 92% of cases. 3/27 (11.1%) underwent abortion and one case had IUFD. 23 newborns were live births (85%) at a mean gestational age (GA) of 34±2 weeks (w). 2 patients died postnatally due to severe associated malformations. Several prenatal parameters were evaluated to differentiate patients with LUTO from non-LUTO, including severity of upper tract dilatation, keyhole sign, oligohydramnios, LBD and GA at diagnosis but none proved predictive of the postnatal diagnosis. Similarly, none of the prenatal parameters evaluated were predictive of postnatal renal function.Diagnosis of megacystis in the second and third trimester was followed by live birth in up to 85% of cases and LUTO was found to be the main cause of fetal megacystis. This potentially more favorable outcome than the majority reported in literature, should be taken into account in prenatal counselling. Megacystis is an often misinterpreted antennal sign that may hide a wide range of diagnoses with different prognoses and not only an increased risk of adverse renal and respiratory outcomes